Adaptive responses of tropical tuna purse-seiners under temporal regulations - Torres-Irineo, Edgar (Ambio, 2016)
The failure to achieve fisheries management objectives has been broadly discussed in international meetings. Measuring the effects of fishery regulations is difficult due to the lack of detailed information. The yellowfin tuna fishery in the eastern Pacific Ocean offers an opportunity to evaluate the fishers’ responses to temporal regulations. We used data from observers on-board Mexican purse-seine fleet, which is the main fleet fishing on dolphin-associated tuna schools. In 2002, the Inter-American Tropical Tuna Commission implemented a closed season to reduce fishing effort for this fishery. For the period 1992–2008, we analysed three fishery indicators using generalized estimating equations to evaluate the fishers’ response to the closure. We found that purse-seiners decreased their time spent in port, increased their fishing sets, and maintained their proportion of successful fishing sets. Our results highlight the relevance of accounting for the fisher behaviour to understand fisheries dynamics when establishing management regulations.